The Ecological Footprint of Poverty Alleviation: Evidence from Mexico's Oportunidades Program - Alix-Garcia, Jennifer; McIntosh, Craig; Sims, Katharine R. E.; Welch, Jarrod R. (The Review of Economics and Statistics, 2013)
We study the consequences of poverty-alleviation programs for environmental degradation. We exploit the community-level eligibility discontinuity for a conditional cash transfer program in Mexico to identify the impacts of income increases on deforestation and use the program's initial randomized rollout to explore household responses. We find that additional income raises consumption of land-intensive goods and increases deforestation. The observed production response and deforestation increase are larger in communities with poor road infrastructure. This suggests that better access to markets disperses environmental harm and that the full effects of poverty alleviation on the environment can be observed only where poor infrastructure localizes them.